Silver-Catalyzed Synthesis of Nitriles from Carboxylic Acids and Cyanamides - Li, Mingsheng; Zi, Lingjian; Chen, Xinqaing; Zhang, Jing (Synlett, 2023)
A concise and practical silver-catalyzed nitrogen-atom-transfer protocol was developed to access versatile nitriles from ubiquitous carboxylic acids with N-cyano-N-phenyl-p-toluenesulfonamide. This protocol complements the established carboxylic acids-to-nitriles conversion methods, which suffer from laborious steps, high temperatures (≥200 °C), or limited substrate scopes. This approach operates broadly across diverse aryl, alkenyl, and primary-, secondary-, or tertiary-alkyl carboxylic acids.
Keywords: carboxylic acids; nitriles; silver; cyanamide; decarboxylation